Individual plant definition and missing plant characterization in vineyards from high-resolution UAV imagery. Issue 1 (1st January 2017) - Primicerio, Jacopo; Caruso, Giovanni; Comba, Lorenzo; Crisci, Alfonso; Gay, Paolo; Guidoni, Silvia; Genesio, Lorenzo; Ricauda Aimonino, Davide; Vaccari, Francesco Primo
ABSTRACT: In the last few years, high-resolution imaging of vineyards, obtained by unmanned aerial vehicle recognitions, has provided new opportunities to obtain valuable information for precision farming applications. While available semi-automatic image processing algorithms are now able to detect parcels and extract vine rows from aerial images, the identification of single plant inside the rows is a problem still unaddressed. This study presents a new methodology for the segmentation of vine rows in virtual shapes, each representing a real plant. From the virtual shapes, an extensive set of features is discussed, extracted and coupled to a statistical classifier, to evaluate its performance in missing plant detection within a vineyard parcel. Passing from continuous images to a discrete set of individual plants results in a crucial simplification of the statistical investigation of the problem.